Polypharmacy in the oldest old (≥80 years of age) patients in China: a cross-sectional study - Xiaoxing Lai; Hongwei Zhu; Xiaopeng Huo; Zheng Li (BMC Geriatrics, 2018)
Abstract Background The oldest old generally have worse health and more comorbidities than the general population of older adults, and they are more likely to be exposed to polypharmacy. Reliable investigation of polypharmacy among the oldest old (≥80 years of age) in China are lacking. So this study aims to describe the polypharmacy status of oldest old patients ≥80 years of age and to assess the factors influencing medication compliance. Methods This was a cross-sectional study of 258 oldest old patients ≥ 80 years of age and hospitalized at a tertiary hospital in Beijing between December 1, 2014 and June 30, 2015. They completed three validated questionnaires to assess their pre-admission status (general demographics, medication knowledge, and medication adherence). Potentially inappropriate medications (PIM) use was evaluated by physicians. Results The majority of the patients (55.4%) took < 10 types of drugs. The numbers of drugs taken ranged from 8 to 60 drugs (median of 22.9). Patients taking 11–20 drugs accounted for 46.1% of the patients. Subjects with a history of adverse drug reactions accounted for 40.3%. The proportion of PIMs was 27.1%. Compliance was only 32.6% among the oldest old patients with polypharmacy. Age and medication classes were independently negatively associated with compliance, and medication knowledge was independently positively associated with compliance. Conclusion Oldest old patients (≥ 80 years of age) had a poor medication knowledge. Age, medication classes, and medication knowledge were independently associated with medication compliance.